Pengaruh Substitusi Daging Ayam Dengan Tempe Terhadap Daya Terima Nuget - Ilham Rizky Putra Wijaya; Eman Darmawan; Masrukan; Dyah Titin Laswati (Universitas Widya Mataram, 2026)
This study aims to determine the effect of tempeh substitution on the chemical, physical, and organoleptic quality of chicken nuggets. The design used was a Completely Randomized Design (CRD) with one factor, namely the tempeh:chicken ratio (0:250, 100:150, 150:100, 200:50, 250:0) and three replications. The parameters tested included water content, ash, protein, fat, crude fiber, texture (chewyness), and organoleptic tests (color, aroma, taste, texture, and overall preference) by 30 panelists. Data were analyzed using ANOVA and further Duncan's Multiple Range Test (DMRT) 5%.The results showed that increasing tempeh substitution decreased the water, ash, and protein content, but increased the fat and crude fiber content. The texture of the nuggets became less chewy, and the organoleptic scores for color, aroma, taste, texture, and liking also decreased. The product most preferred by panelists was a nugget with a composition of 150 g tempeh and 100 g chicken, with a liking score of 3.66. This product has a light golden yellow color (3.63), a distinctive aroma of chicken nuggets (3.63), a chicken nugget taste (3.56), and a slightly hard texture (3.43). The chemical and physical compositions were water content 48.85% (wb), ash 1.61% (db), protein 12.12% (db), fat 4.31% (db), crude fiber 7.37% (db), and elasticity 15.78 mm. This research shows that tempeh has the potential as a raw material for healthy nuggets and an alternative functional food.